Study of the Effectiveness of a Supramolecular Complex Based on Albendazole and Triclabendazole (Altric-Extra) Against Nematodes of the Digestive Tract and Fasciola spp. in Sheep Under Production Conditions - E. V. Lagereva; V. E. Abramov; M. B. Musaev; S. V. Vatsaev; A. Z. Dzhamalova; Kh. I. Bersanova (Российский паразитологический журнал, 2020)
The purpose of the research is to test the effectiveness of the supramolecular complex of albendazole and triclabendazole (Altric-Extra) in case of fasciolosis and nematodoses of the digestive tract of sheep under production conditions.Materials and methods. The test of the effectiveness of Altrik-Extra was carried out in the North Caucasus Federal District of the Chechen Republic in July 2019 on 205 sheep of the Tushino breed, spontaneously infected by gastrointestinal nematodes and Fasciola sp. Sheep infection with helminths was established by fecal examination by Fülleborn using ammonium nitrate. The average number of helminth eggs in 1 g of feces was determined using a VIGIS camera. Altric-Extra was given at a dose of 5 mg/ kg of AS (2.5 mg of albendazole and triclabendazole respectively) or 50 mg/kg in the preparation in a mixture with mixed feed by the group method. The effectiveness of the drug was determined by the results of fecal studies 14 and 25 days after deworming. After giving the drugs for three days, the clinical condition of the experimental sheep was monitored. Altric-Extra effectiveness was evaluated using the “critical test” method according to the Guidelines approved by the World Association for the Progress of Veterinary Parasitology (1995).Results and discussion. The Altric-Extra supramolecular complex in a therapeutic dose of 5.0 mg/kg of AS (for the preparation of 50 mg/kg) was 100% effective against gastrointestinal nematodes and Fasciola sp. of sheep. The sheep ate a mixture of the preparation with mixed feed; it is convenient to set in a group method; side effects after deworming is not observed.